Pro Nerve Growth Factor and Its Receptor p75NTR Activate Inflammatory Responses in Synovial Fibroblasts: A Novel Targetable Mechanism in Arthritis - Farina, Luciapia; Minnone, Gaetana; Alivernini, Stefano; Caiello, Ivan; MacDonald, Lucy; Soligo, Marzia; Manni, Luigi; Tolusso, Barbara; Coppola, Simona; Zara, Erika; Conti, Libenzio Adrian; Aquilani, Angela; et al. (Frontiers in Immunology, 2022)
We have recently provided new evidence for a role of p75NTR receptor and its preferential ligand proNGF in amplifying inflammatory responses in synovial mononuclear cells of chronic arthritis patients. In the present study, to better investigate how activation of the p75NTR/proNGF axis impacts synovial inflammation, we have studied the effects of proNGF on fibroblast-like synoviocytes (FLS), which play a central role in modulating local immune responses and in activating pro-inflammatory pathways. Using single cell RNA sequencing in synovial tissues from active and treatment-naïve rheumatoid arthritis (RA) patients, we demonstrated that p75NTR and sortilin, which form a high affinity receptor complex for proNGF, are highly expressed in PRG4pos lining and THY1posCOL1A1pos sublining fibroblast clusters in RA synovia but decreased in RA patients in sustained clinical remission. In ex vivo experiments we found that FLS from rheumatoid arthritis patients (RA-FLS) retained in vitro a markedly higher expression of p75NTR and sortilin than FLS from osteoarthritis patients (OA-FLS). Inflammatory stimuli further up-regulated p75NTR expression and induced endogenous production of proNGF in RA-FLS, leading to an autocrine activation of the proNGF/p75NTR pathway that results in an increased release of pro-inflammatory cytokines. Our data on the inhibition of p75NTR receptor, which reduced the release of IL-1, IL-6 and TNF-, further confirmed the key role of p75NTR activation in regulating inflammatory cytokine production. In a set of ex vivo experiments, we used RA-FLS and cultured them in the presence of synovial fluids obtained from arthritis patients that, as we demonstrated, are characterized by a high concentration of proNGF. Our data show that the high levels of proNGF present in inflamed synovial fluids induced pro-inflammatory cytokine production by RA-FLS. The blocking of NGF binding to p75NTR using specific inhibitors led instead to the disruption of this pro-inflammatory loop, reducing activation of the p38 and JNK intracellular pathways and decreasing inflammatory cytokine production. Overall, our data demonstrate that an active proNGF/p75NTR axis promotes pro-inflammatory responses in synovial fibroblasts, thereby contributing to chronic synovial inflammation, and point to the possible use of p75NTR inhibitors as a novel therapeutic approach in chronic arthritis.